2019
DOI: 10.3847/1538-4357/ab4a09
|View full text |Cite
|
Sign up to set email alerts
|

Lorentz Factors of Compact Jets in Black Hole X-Ray Binaries

Abstract: Compact, continuously launched jets in black hole X-ray binaries (BHXBs) produce radio to opticalinfrared synchrotron emission. In most BHXBs, an infrared (IR) excess (above the disc component) is observed when the jet is present in the hard spectral state. We investigate why some BHXBs have prominent IR excesses and some do not, quantified by the amplitude of the IR quenching or recovery over the transition from/to the hard state. We find that the amplitude of the IR excess can be explained by inclination dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 140 publications
(162 reference statements)
0
17
0
2
Order By: Relevance
“…The parameter space that we consider here for the optical depth and jet width is determined from the range of values of the parameters that produce good fits to the time lag-photon index correlation in GX 339-4 (Kylafis et al 2008), namely 2 ≤ τ ≤ 5 and 100 r g ≤ R 0 ≤ 500 r g . For γ 0 , we consider the results from Saikia et al (2019), who used the near infrared excess observed in BHBs to constrain the Lorentz factor in the jet in the range 1.3−3.5.…”
Section: Resultsmentioning
confidence: 99%
“…The parameter space that we consider here for the optical depth and jet width is determined from the range of values of the parameters that produce good fits to the time lag-photon index correlation in GX 339-4 (Kylafis et al 2008), namely 2 ≤ τ ≤ 5 and 100 r g ≤ R 0 ≤ 500 r g . For γ 0 , we consider the results from Saikia et al (2019), who used the near infrared excess observed in BHBs to constrain the Lorentz factor in the jet in the range 1.3−3.5.…”
Section: Resultsmentioning
confidence: 99%
“…There are indications that matter in compact jets could be accelerated up to bulk Lorentz factors j ࣠ 3.5 (e.g. Ribó, Dhawan & Mirabel 2004;Russell et al 2015;Péault et al 2019;Saikia et al 2019;Tetarenko et al 2019). No radio emission is usually detected during the soft state, as compact jets are strongly quenched (Fender et al 1999;Corbel et al 2000), by at least 3.5 orders of magnitude (Russell et al 2019a;Maccarone et al 2020).…”
mentioning
confidence: 99%
“…The IR excess usually fades during the hard to HIMS transition (e.g. Coriat et al Bel et al 2011;Saikia et al 2019), with additional brief IR flares only seen close to the hard-HIMS transition if the source does not make a smooth transition (Baglio et al 2018). During the SIMS and soft state the IR emission is quenched as the jet spectrum evolves (e.g.…”
Section: A Brief and Unexpected Ir Flare In The Simsmentioning
confidence: 99%
“…The orbital period is determined to be 26.79377 ± 0.00007 h, and the inclination angle is estimated as 20.7 • ± 1.5 • (Orosz 2003). Russell et al (2006) compiled from the literature a central BH mass of 9.4 ± 1.0 M and a companion mass of 2.45 ± 0.15 M for this system (see also Saikia et al 2019). Its 2002 outburst was monitored regularly with the X-ray satellite Rossi X-ray Timing Explorer (RXTE, Park et al 2004;Kalemci et al 2005Kalemci et al , 2013Reig et al 2006;Gierliński & Newton 2006;Gliozzi et al 2010;Koen 2013;Morningstar & Miller 2014;Dinçer et al 2014;Lipunova & Malanchev 2017;Vahdat Motlagh, Kalemci & Maccarone 2019) and with ground-based optical and IR (Buxton & Bailyn 2004) and radio (Park et al 2004;Kalemci et al 2005) facilities.…”
mentioning
confidence: 99%